2015
DOI: 10.1371/journal.pgen.1004928
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interplay between the 53BP1-Ortholog Rad9 and the Mre11 Complex Regulates Resection, End-Tethering and Repair of a Double-Strand Break

Abstract: The Mre11-Rad50-Xrs2 nuclease complex, together with Sae2, initiates the 5′-to-3′ resection of Double-Strand DNA Breaks (DSBs). Extended 3′ single stranded DNA filaments can be exposed from a DSB through the redundant activities of the Exo1 nuclease and the Dna2 nuclease with the Sgs1 helicase. In the absence of Sae2, Mre11 binding to a DSB is prolonged, the two DNA ends cannot be kept tethered, and the DSB is not efficiently repaired. Here we show that deletion of the yeast 53BP1-ortholog RAD9 reduces Mre11 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 80 publications
6
145
0
2
Order By: Relevance
“…Further characterization of mre11-P110L showed that it is unable to suppress the subtle resection defect of the sae2Δ mutant, and that suppression of the sae2Δ CPT sensitivity is independent of the Mre11 nuclease activity and mostly Exo1 independent. By contrast, yku70Δ restores resection and resistance to DSBinducing agents to the sae2Δ mutant in an Exo1-dependent manner, and rad9Δ suppresses the sae2Δ end resection defect by allowing access to Sgs1-Dna2 (15,23,(38)(39)(40)(41). Deletion of DNL4 (encoding DNA ligase IV) does not suppress the DNA damage sensitivity of sae2Δ, mre11-3, and cpt1Δ mutants, indicating that the yku70Δ suppression is by allowing Exo1 access to ends and not by diverting ends from NHEJ to HR (23,28,38).…”
Section: Discussionmentioning
confidence: 99%
“…Further characterization of mre11-P110L showed that it is unable to suppress the subtle resection defect of the sae2Δ mutant, and that suppression of the sae2Δ CPT sensitivity is independent of the Mre11 nuclease activity and mostly Exo1 independent. By contrast, yku70Δ restores resection and resistance to DSBinducing agents to the sae2Δ mutant in an Exo1-dependent manner, and rad9Δ suppresses the sae2Δ end resection defect by allowing access to Sgs1-Dna2 (15,23,(38)(39)(40)(41). Deletion of DNL4 (encoding DNA ligase IV) does not suppress the DNA damage sensitivity of sae2Δ, mre11-3, and cpt1Δ mutants, indicating that the yku70Δ suppression is by allowing Exo1 access to ends and not by diverting ends from NHEJ to HR (23,28,38).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Sae2, DSB repair is impaired due to prolonged MRX complex binding. This defect is rescued by depleting the yeast 53BP1-ortholog RAD9, as 53BP1 promotes NHEJ by inhibiting dsDNA resection for HR (106, 107). In humans, the tumor suppressor BRCA1 inhibits 53BP1 at breaks in association with MRN and CtIP to promote HR over NHEJ (107110).…”
Section: Mrn and Double-strand Break Repairmentioning
confidence: 99%
“…Rad9 also prevents extensive resection by Exo1 and Dna2-STR at uncapped telomeres (Ngo et al, 2014; Ngo and Lydall, 2010). Elimination of Rad9 can suppress the sae2Δ resection initiation defect by allowing more efficient recruitment of Dna2-STR to DSBs (Bonetti et al, 2015; Ferrari et al, 2015). Similarly, partial loss of function alleles of TEL1 and RAD53 that reduce Rad9 accumulation at DSBs can also suppress the sae2Δ resection defect (Gobbini et al, 2015).…”
Section: Resection and The Dna Damage Checkpointmentioning
confidence: 99%
“…Elimination of Tel1 causes a modest delay in resection initiation while the mec1Δ mutant exhibits increased end resection due to reduced Rad9 recruitment (Clerici et al, 2014; Mantiero et al, 2007). The mechanism by which Rad9 inhibits resection is not fully understood, but is dependent on chromatin association and oligomerization of Rad9 suggesting it forms a physical barrier to Exo1 and Dna2-STR (Ferrari et al, 2015). Activation of Rad53 could also contribute to the Rad9 inhibition of end resection (see below).…”
Section: Resection and The Dna Damage Checkpointmentioning
confidence: 99%